Diagnosa Gejala Kecanduan Bermain Game Online dengan Metode Fuzzy Tsukamoto dan Fuzzy Sugeno - Rivaldi Okta Pratama; Agung Triayudi; Arie Gunawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In this increasingly developing era, online games are a type of game that can provide its own pleasure for its users. Because of that, many people play online games continuously until they forget the time, it can even become addictive. Not many people have the opportunity and willingness to consult an expert to overcome their addiction. Therefore, an expert system is needed to diagnose online game addiction symptoms. With this research, an expert system was produced to diagnose symptoms of addiction to playing online games, which makes it easy to use. This expert system produces output in the form of a diagnosis whether a person is addicted to playing online games or not. Tsukamoto's fuzzy logic method is one method for a good problem solving control system to implement. The Sugeno fuzzy logic used in the expert system in this study functions to seek and find solutions to symptoms of addiction to playing online games. The results of this study can compare the Sugeno fuzzy with the Tsukamoto fuzzy to find the intended value or success by comparing the two fuzzy to find the highest value in this study. The results of this study obtained an accuracy value of 100% from 100 sample data.